PERUBAHAN KADAR SITOKIN DAN MOLEKUL AGREGASI PADA BERBAGAI TINGKAT TROMBOSITOPENIA PADA DEMAM BERDARAH DENGUE - Djunaedi, Djoni (Fakultas Kedokteran Universitas Brawijaya, 2005)
The uncovering of the changes in the concentration of aggregation molecules (vWF, PGI2) and cytokines (TNFα, IL-1β, IL-6) in different levels of thrombocytopenia in DHF patients can be used as the basis in predicting the occurrence of thrombocytopenia. A prospective-observational studywas undertaken utilizing a 3-day sequentially drawn vein blood of inclusive DHF patients. The TNFα, IL-1β and IL-6 test was conducted utilizing the quantikine high sensitivity human cytokine immunoassay, and the vWF and PGI2test was conducted utilizing the ELISA procedure. The multivariate and discriminant analyses tests on the deltas between day 1 and 2 observations, and between day 2 and 3 observations of the 6 variables showed Wilks’ Lambda =0.638 with p=0.008 and platelets and vWF as the most powerful discriminating variable (70.5.%). The findings of this study indicated that in DHF patients (1) the changing of the concentration of TNFα, IL-1βand IL-6 cytokines do not play a significant role in the mechanism of platelets aggregation, (2) platelets count decreases in a condition in which vWF facilitated platelets aggregation, (3) the changing of a positive contribution of vWF causes a determination of the process of platelets aggregation, and (4) a positive changing of vWF’s concentration can be used as a prognostic indicator of a negative changing of platelets count.. Key words: Dengue Hemorrhogic Fever, thrombocytopenia, vWF